REPRESENTATION OF FEAR OF MARRIAGE IN TIKTOK SOCIAL MEDIA WITH #MARRIAGEISSCARY - Sundari, Ismi Putri; Febriana, Poppy (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study examines the phenomenon of fear of marriage expressed through TikTok content with the hashtag #MarriageIsScary, which reflects the changing views of the Indonesian young generation towards the institution of marriage. Method: Using Stuart Hall’s qualitative approach and media representation theory, this study analyzes how narratives, visuals, and elements in TikTok videos shape representations of fear of marriage. Results: The results showed that creators, the majority of Gen Z and millennials, expressed concerns related to gender role inequality, socio-cultural pressures, the burden of expectations, fears of marital failure, changes in the couple’s nature, and past bad experiences that affected their perception of long-term commitments. Social media, particularly TikTok, plays a significant role in reinforcing this view through algorithms that personalize content and provide a space for creative expression for younger generations. The audience’s response to this content is diverse, ranging from full acceptance, a negotiated interpretation, to a rejection of the pessimistic narrative. Novelty: This study confirms that fear of marriage is not only influenced by external factors, but also by deep emotional and relational experiences, and marks a shift in the values and perceptions of younger generations who are more critical and skeptical of marriage as institution social at era digital.